The Position and Role of the Sharia Supervisory Board in Ensuring Sharia Compliance Equity Crowdfunding in Indonesia - Muhammad Habibi Miftakhul Marwa; Sholahuddin Al-Fatih; Mohammad Azam Hussain; Haris Haris (Unissula, 2023)
Fundraising using the equity crowdfunding method has experienced rapid development and is in high demand from the public. In order to maintain the credibility of the implementation of Islamic securities crowdfunding, it is essential to establish a sharia supervisory board to supervise the offering of sharia-compliant securities employing information technology-driven crowdfunding service platforms. This article aims to discuss and analyze the position and role of the sharia supervisory board within the system, as well as the level of compliance with sharia principles in the implementation of equity crowdfunding in Indonesia. The research method used in this article is a type of normative legal research that relies on secondary data sources obtained through a literature review. The legal protection for the existence of a sharia supervisory board in sharia equity crowdfunding in Indonesia is regulated in POJK Number 57/POJK.04/2020 and Fatwa Number 140/DSN-MUI/VIII/2021. The sharia supervisory board has a very strategic role in ensuring sharia compliance in every equity crowdfunding activity in Indonesia. In order to maintain the credibility of sharia equity crowdfunding in the future, it is essential to ensure that every aspect of operations complies with sharia principles by maximizing the existence of a sharia supervisory board.